KEPASTIAN HUKUM MENGENAI TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN - harmaein harmaein; Khalimi Khalimi; Gatut Hendro Tri Widodo (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is motivated by the existence of legal provisions governing corporate social responsibility (CSR), which are expected to contribute to sustainable development, yet in practice various irregularities remain prevalent, including the misuse of CSR funds by several major corporations. The issues examined concern the legal framework of CSR under Law Number 40 of 2007 on Limited Liability Companies and the extent to which legal certainty is ensured in its implementation to achieve sustainable development. The purpose of this study is to analyze the legal construction of CSR and to evaluate its effectiveness and legal certainty in supporting sustainable economic, social, and environmental development. The theoretical foundations employed are the theory of legal certainty and responsive law theory. This research employs a normative legal methodology using the statutory approach, the case approach, and the comparative approach. The data sources consist of primary legal materials such as statutes and government regulations, secondary legal materials including literature, journals, and expert opinions, and tertiary legal materials such as dictionaries and information media. Data were collected through library research, while analysis was carried out using grammatical and systematic interpretation to assess the consistency of CSR provisions with the concept of legal certainty and their implementation in practice. The results of the study indicate that, normatively, the regulation of CSR in Indonesia has a clear legal basis through Law Number 40 of 2007 and Government Regulation Number 47 of 2012. However, the legal certainty of its implementation remains suboptimal due to normative ambiguities, particularly regarding budgeting mechanisms, standards of propriety and reasonableness, and sanctions for companies that fail to implement CSR. Cases of CSR misappropriation further demonstrate weaknesses in oversight and inconsistent enforcement. This research concludes that to realize sustainable development, regulatory strengthening, enhanced transparency, and more effective supervisory mechanisms for CSR implementation are required.